Policy Initiatives on Healthy Ageing in Russia from 2010-2020 - Golubeva, Elena; Emelyanova, Anastasia (European Journal of Mental Health, 2020)
Background: A number of various policy strategies has been adopted in the last decade in response to population ageing in Russia. Governmental actions have yet to be evaluated in terms of their efficacy. By making a detailed overview of policy actions and relevant research, we are able to define successes and failures on the way to having a thriving and healthy older population. Aims: To analyse policy initiatives targeting healthy ageing in terms of both the entire population and the individuals thereof, and provide the overview for the most recent years of 2010–2020. Methods: The study has a theoretical nature. We undertake an analysis of available research literature and policy documents. In Section 2.2.1, we used a systematic literature review approach. Regarding the segment of the collection of literature discussed in the paper, a mixed approach was used retrieving online indexing services and additional searching in the Russian electronic library eLibrary.ru. Results: Main demographic documents and primary structural changes focus on the population decline, ageing, retirement, and overall population health. Research on healthy and active ageing in the Russian academic literature, and elaboration of the new strategies and programs designed specifically for the benefit of older people and their health, have been discussed, with special attention given to the mental health of older people. Conclusion: The initiatives mainly prioritise further increases in life expectancy, the quality of life of older persons, stimulating old-age productivity and active ageing. Many aspects require further improvement such as clear definitions, focused attention to geriatric care, better coordination of managing authorities, sustainable funding, and realistic expectations toward implementation indicators.